Measurement of talent in team handball: The questionable use of motor and physical tests - Lidor, R.; Falk, B.; Arnon, M.; Cohen, Y.; Segal, G.; Lander, Y. (The Journal of Strength and Conditioning Research, 2005)
Testing for selection is one of the most important fundamentals in any multistep sport program. In most ball games, coaches assess motor, physical, and technical skills on a regular basis in early stages of talent identification and development. However, selection processes are complex, are often unstructured, and lack clear-cut theory-based knowledge. For example, little is known about the relevance of the testing process to the final selection of the young prospects. The purpose of this study was to identify motor, physical, and skill variables that could provide coaches with relevant information in the selection process of young team handball players. In total, 405 players (12-13 years of age at the beginning of the testing period) were recommended by their coaches to undergo a battery of tests prior to selection to the Junior National Team. This number is the sum of all players participating in the different phases of the program. However, not all of them took part in each testing phase. The battery included physical measurements (height and weight), a 4 × 10-m running test, explosive power tests (medicine ball throw and standing long jump), speed tests (a 20-m sprint from a standing position and a 20-m sprint with a flying start), and a slalom dribbling test. Comparisons between those players eventually selected to the Junior National Team 2-3 years later with those not selected demonstrated that only the skill test served as a good indicator. In all other measurements, a wide overlap could be seen between the results of the selected and nonselected players. It is suggested that future studies investigate the usefulness of tests reflecting more specific physical ability and cognitive characteristics.